2013
DOI: 10.1111/evj.12188
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ketamine hydrochloride administered as a basilar sesamoid nerve block in alleviating foot pain in horses caused by natural disease

Abstract: Ketamine (3%) administered perineurally for regional anaesthesia of the digit does not desensitise the digit to the same extent as does lidocaine and thus 3% ketamine appears to have no value as a local anaesthetic agent for diagnostic regional anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Bidwell et al [5] conducted a study evaluating the duration of mepivacaine in horses with navicular syndrome using a force plate; they observed complete analgesic effect between 15 and 60 minutes after blockade. Schumacher et al [6] observed inefficacy of ketamine as a local anesthetic agent when compared with lidocaine in abaxial nerve block in horses with chronic lameness evaluated with the aid of a body-mounted inertial sensor system. Differently from the studies mentioned previously, several authors have evaluated the efficacy and duration of local anesthetics using the heat-lamp model to observe the loss of cutaneous sensitivity [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Bidwell et al [5] conducted a study evaluating the duration of mepivacaine in horses with navicular syndrome using a force plate; they observed complete analgesic effect between 15 and 60 minutes after blockade. Schumacher et al [6] observed inefficacy of ketamine as a local anesthetic agent when compared with lidocaine in abaxial nerve block in horses with chronic lameness evaluated with the aid of a body-mounted inertial sensor system. Differently from the studies mentioned previously, several authors have evaluated the efficacy and duration of local anesthetics using the heat-lamp model to observe the loss of cutaneous sensitivity [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Inertial sensor measurements have been shown, through testing with induced lameness models, to be strongly related to lameness [3][4][5][6][7][8][9][10][11][12][13]. Suggesting this exposes a misunderstanding of how this measurement method works.…”
Section: Dear Editormentioning
confidence: 99%
“…We should admit they are only an expert opinion. Inertial sensor measurements have been shown, through testing with induced lameness models, to be strongly related to lameness [3][4][5][6][7][8][9][10][11][12][13]. Drs Bathe, Judy and Dyson state they have experienced cases where reliance on inertial measurement systems, even in skilled hands, has led to conclusions that did not fit with the findings on a thorough conventional work-up.…”
Section: Dear Editormentioning
confidence: 99%